Metaphors of Prophetic Stories in the Quran: A Study of Ahmad Muhammad Khalafullah's Imagination with al-Ghazali's Epistemology - Kumala, Salisa Wardah; Riyadi, Abdul Kadir (QiST: Journal of Quran and Tafseer Studies, 2025)
This study examines the interpretation of the stories of the prophets in the Qur'an through an epistemological critique of Ahmad Muhammad Khalafullah's literary-historical approach using al-Ghazālī's theory of imagination (al-khayāl). Although there has been extensive discussion of the narratives of the prophets in the Qur'an and literary approaches, previous studies have rarely examined the epistemological implications of imagination within Khalafullah's literary-historical framework, particularly in relation to the ontological truth of revelation. Khalafullah places the imaginative dimension in Qur'anic stories as a literary element that does not depend on historical truth, thus raising debates about the ontological status of revelatory stories. Meanwhile, al-Ghazālī, through Mishkāt al-Anwār and Iḥyā' ‘Ulūm al-Dīn, asserts that imagination is an epistemic medium that connects sensory reality and spiritual essence, so it cannot be reduced to fiction. This study aims to critically reassess Khalafullah's position by employing al-Ghazali's hierarchical epistemology of truth. This study employs a qualitative literature based method with descriptive critical analysis of primary works of Khalafullah and al-Ghazali, supported by contemporary Quranic studies. The findings demosntrate that al-Ghazālī's epistemology of al-khayāl offers a corrective framework to Khalafullah's reductionist tendency by situating Qur'anic narratives within a layered structure of truth encompassing literal, moral, and spiritual dimensions. This integrative framework preserves the pedagogical function of imagination without negating the ontological status of revelation. This study contributes to strengthening contemporary interpretation methodology by offering an integrative perspective between literary aspects and revelatory truth. At an international level, the study offers a conceptual alternative for ongoing debates on scripture, narrative, and imagination across Islamic Studies, religious, hermeneuthics, and comparative theology.